Analisis Peningkatan Angka Partisipasi Mahasiswa Melalui Pengembangan Materi Digital Marketing Di Lingkungan Universitas Terbuka - Pramudibyanto, Hascaryo Pramudibyanto; Miandhiani Deniz Y (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
This study employs a descriptive-comparative method to compare two main strategies, namely Digital PR and Digital Marketing, implemented in the environment of Universitas Terbuka Semarang. Data were collected through interviews with university staff involved in the implementation of both strategies, document analysis, and observation of university practices. The Digital PR strategy at UT Semarang focuses on building a positive image through social media, online news platforms, and blogs, while the Digital Marketing strategy emphasizes paid advertising, paid social media, and email campaigns to prospective students. The integration of both strategies was then evaluated to determine the resulting outcomes, revealing that the combined strategies generated a consistent and robust narrative that enhanced the conversion of prospective students into new students. Despite positive outcomes, the study identified challenges such as the expansion of resources and workforce needed to execute effective digital campaigns. The research subjects were twelfth-grade students at SMA N 1 Ungaran who were active on social media with over 1,000 followers, selected using purposive sampling techniques. Three students were chosen as research subjects because they were considered potential influencers in the Ungaran area.